Immunomodulatory Effect of a New Ingredients Group Extracted from Astragalus Through Membrane Separation Technique - Zhang D; Guo Y; Wang Y (Dove Medical Press, 2021)
Di Zhang,1,* Yafei Guo,2,* Yingli Wang2 1Department of Basic Medicine, Shanxi Medical University, Taiyuan, People’s Republic of China; 2Department of Traditional Chinese Medicine and Food Engineering, Shanxi University of Traditional Chinese Medicine, Jinzhong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Di Zhang Email zhangdi0801@live.cnIntroduction: Astragalus is a commonly used traditional Chinese medicine in China, which has been widely applied to enhance the immunomodulatory function of the body. The main bioactive components are complicated. To explore the role of the components, various techniques have been applied in Astragalus extraction. Membrane separation technique featured with green processing condition and high efficiency is of signification interest in the application of Astragalus treatment.Methods: In this study, a new ingredients group A4 was separated from Astragalus using membrane separation technique. The quantification and identification of A4 were achieved by UV-vis spectrometry and UPLC-MS measurements. Pathological approaches along with serum metabolomics were utilized to study the immunoprotective effects of the extracts and explore the underlying mechanisms on metabolic activity.Results: It was observed that A4 could promote the secretion of IL-2 and IFN-γ, stimulate the activated CD4+CD25+ and CD8+ CD25+ T lymphocytes in splenocytes and protect rat spleen to some extent. Seven crucial biomarkers that related to immunity regulations were screened out and identified through serum metabonomic analysis coupled with nuclear magnetic resonance. The enrichment analysis revealed that A4 alleviated the immune dysfunction by modulating amino acid metabolism and energy metabolism for the first time.Conclusion: The new ingredients group A4 isolated from the Astragalus membrane can reduce the immune dysfunction by regulating the amino acid metabolism and energy metabolism of rats.Keywords: Astragalus, membrane separation, immunomodulatory, serum metabolomics